Three-dimensional displacement field of the 2010 Mw 8.8 Maule earthquake from GPS and InSAR data with the improved ESISTEM-VCE method - Xiong, Luyun; Xu, Caijun; Liu, Yang; Zhao, Yingwen; Geng, Jianghui; Ortega-Culaciati, Francisco (Frontiers in Earth Science, 2022)
The 2010 Mw 8.8 Maule earthquake occurred offshore central Chile and ruptured ~500 km along the subduction that oceanic Nazca plate subducting beneath the continental South American plate. It is a great challenge to extract its accurate three-dimensional coseismic deformation field with high spatial resolution. In this study, we modified the extended simultaneous and integrated strain tensor estimation from geodetic and satellite deformation measurements (ESISTEM) method with variance component estimation algorithm (ESISTEM-VCE) to retrieve the three-dimensional surface displacement field of this event by integrating the interferometric synthetic aperture radar (InSAR) and global positioning system (GPS) measurements. The ESISTEM-VCE method not only can take into account the spatial correlation of surface displacement among the adjacent points and determine the accurate weight ratios for different data sets, but also can make use of the uncertainty of GPS data and consider the different spatial scales from different data sources. In the simulation experiments, the RMSEs of the ESISTEM-VCE method are the smallest, and the improvements of 97.1%, 3.9%, and 84% are achieved in the east-west, north-south, and vertical components, respectively. Then, it is applied to the real case study of the 2010 Mw 8.8 Maule earthquake. The three-dimensional displacement field could provide fine deformation information. In the east-west component, the significant deformation is in the north of the epicenter, closed to the Constitución, with a maximum westward displacement of 495.5 cm. The displacement in the north-south component is relatively small compared to that in the east-west component. The maximum uplift reaches 211.8 cm, located at the southwest of the Concepción. Finally, the derived vertical displacements are also compared with field investigations, indicating that the ESISTEM-VCE method can obtain more accurate weight and perform better. The results highlight that the earthquake ruptured along NE-SW direction, with a dominant thrust and a relatively small component of right-lateral strike-slip, coinciding with the characteristics of subduction and right-lateral shear. The experiments with the simulated and real data suggest that the modified ESISTEM-VCE method in this study is feasible and effective.